High frequency trading and comovement in financial markets - Malceniece, Laura; Malcenieks, Kārlis; Putniņš, Tālis J. (Journal of Financial Economics, 2019)
Using the staggered entry of Chi-X in 12 European equity markets as a source of exogenous variation in high frequency trading (HFT), we find that HFT causes significant increases in comovement in returns and in liquidity. About one-third of the increase in return comovement is due to faster diffusion of market-wide information. We attribute the remaining two-thirds to correlated trading strategies of HFTs. The increase in liquidity comovement is consistent with HFT liquidity providers being better able to monitor other stocks and adjust their liquidity provision accordingly. Our findings suggest a channel by which HFT impacts the cost of capital.